2020
DOI: 10.3389/fonc.2020.00430
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Baseline Neutrophil Count and Lactate Dehydrogenase Level in Patients With Esophageal Squamous Cell Cancer Treated With Radiotherapy

Abstract: Background: This present study aimed to explore the prognostic value of pretreatment neutrophil and lactate dehydrogenase (LDH) and to develop a prognostic risk scoring model to predict prognosis in esophageal squamous cell cancer (ESCC) patients treated with definitive radiotherapy. Methods: Retrospectively collected data of patients who received definitive radiotherapy for ESCC at Shantou Central Hospital between January 2009 and December 2015 were included for the analysis. The association between the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Additionally, an investigation that recruited 567 ESCC patients by Luo HS et al has also demonstrated that an elevated LDH level was an independent indicator for poor prognosis. 20 To sum up, though no agreement regarding pretreatment serum LDH level was the predictor for prognosis in ESCC, it may be a reliable factor in predicting the therapeutic effect of chemoradiotherapy in patients with ESCC according to our results. More researches are warranted to further validation before widely used in clinical settings.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Additionally, an investigation that recruited 567 ESCC patients by Luo HS et al has also demonstrated that an elevated LDH level was an independent indicator for poor prognosis. 20 To sum up, though no agreement regarding pretreatment serum LDH level was the predictor for prognosis in ESCC, it may be a reliable factor in predicting the therapeutic effect of chemoradiotherapy in patients with ESCC according to our results. More researches are warranted to further validation before widely used in clinical settings.…”
Section: Discussionmentioning
confidence: 55%
“…[8][9][10][11][12][13][14]25 Several studies also have evaluated the prognostic value of LDH in ESCC. [15][16][17][18][19][20] Nevertheless, the prognostic role for pretreatment serum LDH in ESCC remains uncertain until now. The current study demonstrated that lower LDH levels were associated with a better prognosis compared with higher LDH levels, as shown in both multivariable analysis based on the whole cohort of 614 patients and the propensity score-matched cohort of 256 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils potentially promote cancer progression (30), and lymphocytes play a key role in mediating tumoricidal effects (26). NLR has been used as valuable biomarker to predict the survival outcomes of patients with esophageal cancer, regardless of whether they were treated surgically or with RT (20)(21)(22)31,32). We determined the OS correlation with NLR-b and NLR-h, and found the optimal cut-off value for NLR-b is 3.68.…”
Section: Discussionmentioning
confidence: 99%